2019
DOI: 10.1123/iscj.2017-0094
|View full text |Cite
|
Sign up to set email alerts
|

Coach Burnout: A Scoping Review

Abstract: 35Coaches' experiences of burnout and stress have been popular topics for research within sport 36 psychology, particularly over the last decade. The purpose of this scoping review was to provide 37 an up-to-date and critical review of the coaching burnout literature, consolidate research 38 findings, assess current methodological and conceptual trends, and identify avenues for research 39 in this area. Five electronic databases were used to conduct the literature search up to September 40 30 th , 2017 (PsycIN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
64
1
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(71 citation statements)
references
References 74 publications
2
64
1
4
Order By: Relevance
“…Thus, job insecurity is a normalized, integral part of this profession [ 93 ]. Consequently, HPC research has paid attention to stress, burnout, and mental health [ 5 ] but job insecurity has received limited attention. A recent study from Spain, including a large coach population ( N = 1481) representing different levels, found that insecurity over working conditions and emotional demands was significantly elevated as compared with reference values of the Spanish general work force [ 94 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Thus, job insecurity is a normalized, integral part of this profession [ 93 ]. Consequently, HPC research has paid attention to stress, burnout, and mental health [ 5 ] but job insecurity has received limited attention. A recent study from Spain, including a large coach population ( N = 1481) representing different levels, found that insecurity over working conditions and emotional demands was significantly elevated as compared with reference values of the Spanish general work force [ 94 ].…”
Section: Discussionmentioning
confidence: 99%
“…High performance coaches (HPCs) report a combination of frequently occurring stressors within the personal, organizational, and competitive domains [ 3 , 4 ]. Consequently, it has been suggested that being an HPC is an all-consuming and demanding profession without clear boundaries, which can ultimately be detrimental to their mental health [ 4 , 5 , 6 ]. The increasingly competitive and evaluative nature of elite sport fosters performance expectations that are associated with harsh scrutiny, criticism, and job insecurity [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is especially relevant for bigger team sports such as football, which also involve thousands (sometimes millions) of engaged and passionate fans, media, stakeholders, and sponsors. Indeed, high performance coaching in general is a profession that is vulnerable to mental health problems [3] and in particular football [4][5][6].…”
Section: Introductionmentioning
confidence: 99%